Exploring the causal relation between obesity and alcohol use, and educational outcomes - Vuik, Sabine (OECD Publishing, 2019)
Two of the most important health risk factors for children and young adults are obesity and alcohol use. These risk factors are known to affect health and wellbeing, but may also have an impact on educational outcomes. The objective of this study was to assess a potential causal relationship between obesity or alcohol use, and educational outcomes, in Germany, the Netherlands, New Zealand, the Russian Federation, the United Kingdom, and the United States. Longitudinal data from cohort studies was used to establish temporal precedence. To ensure the absence of alternative explanations, regression models were adjusted for known confounders; instrumental variables were used to address endogeneity caused by reverse causality and potential unobserved confounders; and fixed effects analyses were used to correct for unobserved time-invariant confounders. The results suggest that the presence of obesity during childhood, as well as alcohol consumption during childhood, can have a negative impact on educational performance and future educational attainment
Keywords: Social Issues/Migration/Health